2020
DOI: 10.1186/s13052-020-0795-7
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on parenting stress of children with cystic fibrosis

Abstract: Background: The management of chronic diseases, particularly in children, requires an integrated physical and psychological approach to both sick children and their family. This is the case of Cystic Fibrosis (CF), a complex genetic chronic disease, where, a comprehensive evaluation of the emotional impact and an effective multidimensional approach are indicated. Aim: This study investigates on parenting stress in children and adolescents with CF and its determinants related to parents, children and the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…24 As the presence of an accompanying chronic illness that primarily affects the immune and respiratory systems would likely increase the anxiety level to a greater degree in the caregivers of healthy children, this was an expected finding. 25 Malnutrition was reported to be an independent factor that negatively affects survival. 26 One of the aims of the present study was to determine the nutritional status of the CF patients via telehealth services and intervene as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…24 As the presence of an accompanying chronic illness that primarily affects the immune and respiratory systems would likely increase the anxiety level to a greater degree in the caregivers of healthy children, this was an expected finding. 25 Malnutrition was reported to be an independent factor that negatively affects survival. 26 One of the aims of the present study was to determine the nutritional status of the CF patients via telehealth services and intervene as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, healthcare professionals, must be able to manage their emotions in difficult situations involving both patients and parents. 5,6 Soft skills are fundamentally based on the following: 7,8 • Interpersonal skills: active listening, good relationships, being useful, conflict resolution and mediation, negotiation, persuasion and influencing skills, team-working, problem solving and decision-making. • Organizational skills: time management, the ability to complete activities multitask, the ability to achieve goals and follow guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, healthcare professionals, must be able to manage their emotions in difficult situations involving both patientsand parents. 5 , 6 Soft skills are fundamentally based on the following: 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Psychological symptoms in both individuals with CF and parent caregivers have been associated with decreased lung function, lower body mass index, worse adherence, worse health-related quality of life, more frequent hospitalizations, and increased healthcare costs [ 223 ]. Continisio et al [ 224 ] showed a significant presence of stress in females (60.23%), subjects married (84.62%), unemployed subjects (69.23%) and "middle School" education levels (61.54%). Authors also highlighted a positive correlation between clinical severity and total stress, i.e., an increase of abnormal stress was found in parents who were concerned because of severe course of the disease in their kids.…”
Section: Introductionmentioning
confidence: 99%